2011
DOI: 10.1152/ajpheart.00353.2011
|View full text |Cite
|
Sign up to set email alerts
|

The rate of O2loss from mesenteric arterioles is not unusually high

Abstract: Golub AS, Song BK, Pittman RN. The rate of O2 loss from mesenteric arterioles is not unusually high. Am J Physiol Heart Circ Physiol 301: H737-H745, 2011. First published June 17, 2011 doi:10.1152/ajpheart.00353.2011The O 2 disappearance curve (ODC) recorded in an arteriole after the rapid arrest of blood flow reflects the complex interaction among the dissociation of O 2 from hemoglobin, O 2 diffusivity, and rate of respiration in the vascular wall and surrounding tissue. In this study, the analysis of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…Recent reports by Golub et al . have demonstrated that the transmural gradient in PO 2 for arterioles is small , only a few mmHg confirming the original report by Duling and Berne , and that the rate of loss of oxygen from mesenteric arterioles is not unusually high .…”
Section: Application Of Optical Techniques To Study Oxygen Transport supporting
confidence: 83%
See 1 more Smart Citation
“…Recent reports by Golub et al . have demonstrated that the transmural gradient in PO 2 for arterioles is small , only a few mmHg confirming the original report by Duling and Berne , and that the rate of loss of oxygen from mesenteric arterioles is not unusually high .…”
Section: Application Of Optical Techniques To Study Oxygen Transport supporting
confidence: 83%
“…Thus, the large transmural gradient in PO 2 reported by Tsai et al . appears to be the failure to apply a large correction, for the oxygen consumption by the method, to their measurements and so the conclusion that the arteriolar wall is a major sink for oxygen consumption is called into question .…”
Section: Application Of Optical Techniques To Study Oxygen Transport mentioning
confidence: 99%
“…The measurement of ISF PO 2 was undertaken because, had vasoconstriction been measured after HBOC-201 or its modifications, then it would have determined whether or not the test fluid was providing adequate oxygen to the tissue despite the vasoconstriction (Golub & Pittman, 2012). The observed interstitial PO 2 values for skeletal muscle were consistent with other studies indicating adequate accuracy in our tissue oxygenation technique (Shibata et al, 2001; Golub et al, 2007; Golub et al, 2011; Song et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
“…PO 2 was related to the rate of phosphorescence decay, K, according to the Stern-Volmer equation, K = Ko + Kq PO 2 , where the values of the calibration constants for Oxyphor R2 were Ko = 1.53×10 −4 μs −1 and Kq = 4.3×10 −4 μs −1 mmHg −1 . Details of the phosphorescence quenching microscopy technique have been previously published (Golub et al, 2007; Golub et al, 2011, Golub & Pittman, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…We produced several podcasts in the field of vascular biology and microcirculation (7, 8, 10, 23,33,34,39,41,53,57,58,67,76,105,106,115,116), and we wish to highlight several key podcasts here. We discussed a human study that looked at the central blood pressure response to the cyclooxygenase inhibitor indomethacin in both old and young healthy adults (5), which addressed the question: What happens when you combine nonsteroidal anti-inflammatory drug-type pain medication and aging-induced arterial stiffening?…”
Section: Podcastsmentioning
confidence: 99%